Faktor-Faktor Yang Mempengaruhi Penghindaran Pajak (Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2019) - subadriyah subadriyah; Ismi Tri Rahayu (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
Abstract:. This research was conducted with the aim of knowing and testing the effect of financial ratios namely Profitability, Capital Intensity, Leverage, and Liquidity on Tax Avoidance (in Consumer Goods Industry Manufacturing Companies Listed on idx in 2016-2019). Sample determination is done using purposive sampling techniques and obtained as many as 30 companies that meet the criteria. The data used is secondary data obtained from financial statements published by the company in www.idx.co.id. The study used multiple linear regression analysis. The results of this study showed that the variables of Profitability, Capital Intensity, Leverage, and Liquidity had no significant effect on Tax Avoidance. But each variable has a coefficient that is negative. The ability of independent variables to influence dependent variables by 4.4% and the remaining 95.6% is explained by variables and beyond regression.